Uptake Pathways to Achieve Gender-Responsive Breeding - CGIAR Research Program on Roots, Tubers and Bananas (CGIAR System Organization, 2018)
This brief describes the key outputs from the CGIAR Gender and Breeding Initiative, and the desired outcomes that the Initiative aims to achieve in order to improve the gender-responsiveness of plant and animal breeding programs.